CD8+ T cells are necessary for improved sepsis survival induced by CD28 agonism in immunologically experienced mice - Anyalebechi, Jerome C.; Sun, Yini; Davis, Carolyn; Wagener, Maylene E.; Liang, Zhe; Burd, Eileen M.; Coopersmith, Craig M.; Ford, Mandy L. (Frontiers in Immunology, 2024)
Introduction: A hallmark of T cell dysregulation during sepsis is the downregulation of costimulatory molecules. CD28 is one of T cell costimulatory molecules significantly altered on memory T cells during sepsis. We recently showed that treatment with a αCD28 agonist in septic immunologically experienced mice led to improved survival. Therefore, here we aimed to identify the cell subset(s) necessary for the survival benefit observed in the context of CD28 agonism, and to further investigate the mechanism by which CD28 agonism improves sepsis survival in immunologically experienced mice. Methods: Mice received specific pathogen inoculation to generate memory T cell populations similar in frequency to that of adult humans. Once these infections were cleared and the T cell response had transitioned to the memory phase, animals were rendered septic via cecal ligation and puncture in the presence or absence of an agonistic anti-CD28 mAb.Results: Results demonstrated that CD8 + T cells, and not bulk CD4 + T cells or CD25 + regulatory T cells, were necessary for the survival benefit observed in CD28 agonist-treated septic immunologically experienced mice. Upon examination of these CD8 + T cells, we found that CD28 agonism in septic immunologically experienced mice was associated with an increase in Foxp3 + CD8 + T cells as compared to vehicle-treated controls. When CD8 + T cells were depleted in septic immunologically experienced mice in the setting of CD28 agonism, a significant increase in levels of inflammatory cytokines in the blood was observed.Discussion: Taken together, these results indicate that CD28 agonism in immunologically experienced mice effectively suppresses inflammation via a CD8 + -dependent mechanism to decrease mortality during sepsis.